SURVIVAL RATE BENIH IKAN PAPUYU (Anabas testudineus Bloch) DENGAN PEMBERIAN VARIASI PROBIOTIK - Anny Rimalia (Fakultas Pertanian UVAYA Banjarmasin, 2024)
This study aimed to evaluate the effect of different doses of Lactobacillus casei probiotics on the survival rate of climbing perch (Anabas testudineus Bloch) larvae. The research was conducted at the researcher’s residence for 10 days, using aquariums measuring 40 x 25 x 25 cm filled with 15 liters of water. The papuyu fish larvae used had a length ranging from 3 to 5 cm, with 10 fish per aquarium. The study employed an experimental method with a Completely Randomized Design (CRD) consisting of three treatments and three replicates. The treatments involved spraying 1 ml, 2 ml, and 4 ml doses of Lactobacillus casei probiotics on commercial feed. The results showed that the survival rate of climbing perchlarvae was 100% across all treatments. Water quality parameters such as pH, temperature, dissolved oxygen, and ammonia remained within tolerable limits for the fish throughout the study. Based on these findings, it can be concluded that varying doses of Lactobacillus casei probiotics did not significantly affect the survival rate of climbing perchlarvae